Algorithms for management of patients with severe A/H1N1 influenza: from diagnosis to respiratory support techniques. Guidelines - Sergey N. Avdeev; Andrey A. Zaytsev; Konstantin V. Zhdanov; Mikhail B. Patsenko; Sergei A. Chernov; Valerii V. Stets; Nikolai P. Potekhin; Aleksander A. Sergoventsev; Denis V. Davydov; Evgeniy V. Kryukov; Vladimir A. Chernetsov (ZAO "Consilium Medicum", 2023)
In 2022, the incidence of swine (A/H1N1) influenza markedly increased. It causes acute lung injury similar to that caused by SARS-CoV-2. These practice guidelines focus on the management of patients with severe influenza: from the diagnostic algorithm to the specifics of therapy and the use of respiratory support techniques. The guidelines provide recommendations on the rational pharmacotherapy principles: antiviral, antibacterial, mucoactive, anticoagulant, and symptomatic. The need to avoid prescribing drugs that may worsen the condition of patients with A/H1N1 influenza that are effective in other viral lung diseases, including SARS-CoV-2, has been pointed out. A detailed review of the criteria for initiation and principles of respiratory support is given.